Comparison of the RNA-based EndoPredict multigene test between core biopsies and corresponding surgical breast cancer sections. Issue 7 (23rd March 2012) - Müller, Berit Maria; Brase, Jan C; Haufe, Franziska; Weber, Karsten E; Budzies, Jan; Petry, Christoph; Prinzler, Judith; Kronenwett, Ralf; Dietel, Manfred; Denkert, Carsten
Abstract : Aim: This study compared the perfomance of the RNA-based EndoPredict multigene test on core biopsies and surgical breast cancer specimens and analysed the influence of biopsy-induced tissue injuries on the test result. Methods: 80 formalin-fixed paraffin-embedded samples comprising paired biopsies and surgical specimens from 40 ER-positive, HER2-negative patients were evaluated. Total RNA was extracted and the EndoPredict score was determined. Results: RNA yield was considerably lower in core biopsies, but sufficient to measure the assay in all samples. The EndoPredict score was highly correlated between paired samples (Pearson r=0.92), with an excellent concordance of classification into a low or high risk of metastasis (overall agreement 95%). Conclusions: The measurements are comparable between core biopsies and surgical sections, which suggest that the EndoPredict assay can be performed on core biopsy tissue. Inflammatory changes induced by presurgical biopsies had no significant effect on the RNA-based risk assessment in surgical specimens.